RESEARCH OF THE NATURE OF TRANSPORTATION IN UKRAINE BY ROAD TRANSPORT - Sokhatsky, Anatoly V. (Systems and Technologies, 2022)
Summary. Real flows around vehicles are turbulent. To date, there are no universal mathematical models of turbulence in computational aerodynamics. Reliable prediction of the characteristics of turbulent flows is an extremely important scientific problem and is associated with the complexity and insufficient study of turbulence as a physical phenomenon.The paper considers approaches based on the use of Reynolds Averaged Navier – Stokes – RANS equations; two classical approaches – Direct Numerical Simulation (DNS) and Large Eddy Simulation (LES); hybrid approaches based on the joint use of RANS and LES methods for different flow regions.Based on the capabilities of modern computing technology, hybrid methods remain the most accessible. They are based on the joint use of RANS and LES approaches in different areas of the flow.